Small in Size, but Large in Action: microRNAs as Potential Modulators of PTEN in Breast and Lung Cancers - Asal Jalal Abadi; Ali Zarrabi; Mohammad Hossein Gholami; Sepideh Mirzaei; Farid Hashemi; Amirhossein Zabolian; Maliheh Entezari; Kiavash Hushmandi; Milad Ashrafizadeh; Haroon Khan; Alan Prem Kumar (Biomolecules, 2021)
MicroRNAs (miRNAs) are well-known regulators of biological mechanisms with a small size of 19–24 nucleotides and a single-stranded structure. miRNA dysregulation occurs in cancer progression. miRNAs can function as tumor-suppressing or tumor-promoting factors in cancer via regulating molecular pathways. Breast and lung cancers are two malignant thoracic tumors in which the abnormal expression of miRNAs plays a significant role in their development. Phosphatase and tensin homolog (PTEN) is a tumor-suppressor factor that is capable of suppressing the growth, viability, and metastasis of cancer cells via downregulating phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling. PTEN downregulation occurs in lung and breast cancers to promote PI3K/Akt expression, leading to uncontrolled proliferation, metastasis, and their resistance to chemotherapy and radiotherapy. miRNAs as upstream mediators of PTEN can dually induce/inhibit PTEN signaling in affecting the malignant behavior of lung and breast cancer cells. Furthermore, long non-coding RNAs and circular RNAs can regulate the miRNA/PTEN axis in lung and breast cancer cells. It seems that anti-tumor compounds such as baicalein, propofol, and curcumin can induce PTEN upregulation by affecting miRNAs in suppressing breast and lung cancer progression. These topics are discussed in the current review with a focus on molecular pathways.